THE ROLE OF CUSTOMER TRUST IN MEDIATING INFLUENCE OF BRAND IMAGE AND BRAND AWARENESS OF THE PURCHASE INTENTION IN AIRLINE TICKETS ONLINE - Pramudya, Arya Krisna; Sudiro, Achmad; Sunaryo, Sunaryo (Jurnal Aplikasi Manajemen, 2018)
Developments in technology, has facilitated the public in obtaining information. One of the information technologies is the internet which penetrated into every aspect of life, especially in the world of business. The progress in the information technologies has increased business competition, particularly in the airline industry. The purpose of this study was to obtain empirical evidence related to the role of customer trust in mediating influence of brand image and brand awareness of the purchase intention in airline tickets online. This study using SEM analysis (Structural Equation Model) with the number of samples is 140. The object of this research is that consumers in one of the governmentowned airline company in Indonesia (Flag Carrier). The results showed that the corporate image has an influence on customer trust. Brand awareness has effects on customer trust and purchase intention. Customer trust has an influence on purchase intention. The customer trust is able to mediation and gives the influence of the corporate image on purchase intention. Indications and implications of the results of these studies are discussed further in this article.